2020
DOI: 10.15570/actaapa.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

A case report and differential diagnosis of pruritic pretibial skin lesions

Abstract: Pretibial pruritic papular dermatitis (PPPD) is a clinical entity first described in 2006. The etiology is uncertain; however, gentle chronic rubbing is likely to be the reason for the skin reaction. Pretibial pruritic lesions may reflect many different systemic diseases and dermatoses. We present a 61-year-old patient with a 2-year history of pruritic pretibial xerosis, keratotic erythematous to brownish papules, and excoriations. Differential diagnosis excluded papular mucinosis, myxoedema, stasis dermatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
(13 reference statements)
0
8
1
Order By: Relevance
“…Chronic scratching or rubbing of the skin leads to variable cutaneous disorders. 2 PPPD is a recently recognized entity as a distinctive response to persistent gentle rubbing of pretibial skin. 1 After the first introduction by Annessi et al in 2006, 1 4 cases of PPPD were subsequently reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chronic scratching or rubbing of the skin leads to variable cutaneous disorders. 2 PPPD is a recently recognized entity as a distinctive response to persistent gentle rubbing of pretibial skin. 1 After the first introduction by Annessi et al in 2006, 1 4 cases of PPPD were subsequently reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“… 1 After the first introduction by Annessi et al in 2006, 1 4 cases of PPPD were subsequently reported in the literature. 2–4 The condition commonly presents as multiple, intensely pruritic, discrete, smooth-surface, flesh-colored to erythematous papules that may subsequently coalesce into plaques and result in a cobblestone appearance. 1 , 2 , 4 , 5 However, in 2019, Flores et al broadened the clinical and histological spectrum of PPPD in 38 patients, demonstrating its epidermal changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is in differential diagnosis with: keratosis pilare (KP), prurigo nodularis (PN) [8], xanthomas, perforating dermatoses (collagenoses), lichen planus, mycosis fungoides [2], papular mucinosis, myxedema, stasis dermatitis [9], lichen simplex chronicus (LSC) and pretibial pruritic papular dermatitis [6].…”
mentioning
confidence: 99%